2012
DOI: 10.1017/jfm.2011.543
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pitching of an elastic rectangular wing in hovering motion

Abstract: In order to study the role of the passive deformation in the aerodynamics of insect wings, we computationally model the three-dimensional fluid-structure interaction of an elastic rectangular wing at a low aspect ratio during hovering flight. The code couples a viscous incompressible flow solver based on the immersedboundary method and a nonlinear finite-element solver for thin-walled structures. During a flapping stroke, the wing surface is dominated by non-uniform chordwise deformations. The effects of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
96
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 35 publications
(42 reference statements)
14
96
1
Order By: Relevance
“…This observation is consistent with the finding in [34]. We also noted that in a recent study [52] on the role of flexibility in the hovering performance of a rectangular flapping wing, the maximum lift and efficiency (lift-to-power ratio) were also achieved at a forcing frequency much lower than the resonance point (around x ¼ 0:25-0:35).…”
Section: Resonance and Performance Optimumsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with the finding in [34]. We also noted that in a recent study [52] on the role of flexibility in the hovering performance of a rectangular flapping wing, the maximum lift and efficiency (lift-to-power ratio) were also achieved at a forcing frequency much lower than the resonance point (around x ¼ 0:25-0:35).…”
Section: Resonance and Performance Optimumsupporting
confidence: 92%
“…It is interesting to note that a similar trend has also been reported in some studies of the flexibility effect on hovering performance of flapping foils or wings [19,52]. In these works, the maximum lift production was achieved at a moderate flexibility.…”
Section: Effects Of Flexibility On Propulsive Performancesupporting
confidence: 82%
“…A fixed, non-uniform, single-block Cartesian grid is employed to discretize the domain (figure 2a). The rectangular domain is 20 Â 20 Â 18 cm The numerical method has been previously validated for flapping-wing simulations against both experimental and simulation data in Dai et al [20], where a fruit fly model and an impulsively started plate were studied. To further validate the model in this work, we compare the flow field with that obtained from the PIV experiment by Warrick et al [10].…”
Section: Simulation Set-up and Model Validationmentioning
confidence: 99%
“…Recently, great theoretical, experimental, and computational efforts have been directed towards advancing our understanding of flexible-wing propulsion [33,2,4,84,88,79,19,57,89,72]. These studies have demonstrated that flexibility can drastically improve propulsive performance, especially when a wing or fin is driven near resonance [51,50,21,54,69].…”
Section: Introductionmentioning
confidence: 99%